Comparison of neuroprotective effects of extract and fractions from Agarum clathratum against experimentally induced transient cerebral ischemic damage. (March 2014) - Kim, In Hye; Yoo, Ki-Yeon; Park, Joon Ha; Yan, Bing Chun; Ahn, Ji Hyeon; Lee, Jae-Chul; Kwon, Hyuk Min; Kim, Jong-Dai; Kim, Young-Myeong; You, Sang Guan; Kang, Il-Jun; Won, Moo-Ho
Abstract Contexts: Agarum clathratum (Laminariaceae), a typical brown algae, has been identified by National Plant Quarantine Service in Korea. The extract of A. clathratum has antioxidant activities. Objective: We investigated the neuroprotective effects of crude-extract, ethyl acetate (EA)-, n-butanol (BU)-, dichloromethane (DCM)- and n-hexane (Hx)-fractions from A. clathratum on ischemic damage in the gerbil hippocampal CA1 region (CA1) after 5 min of transient cerebral ischemia. Materials and methods: Agarum clathratum was collected in Kangwon province (South Korea) and treated with 95% ethanol. The ethanol extract was suspended in distilled water and subjected to a series of partitions with EA, BU, DCM and Hx. Each of extract and fraction was orally administered with 50 mg/kg once a day for one week before ischemia--reperfusion (I-R). Result: In the crude-extract-, EA- and BU-fraction-treated ischemia groups, we found strong neuroprotection in the CA1 – about 80–89% of CA1 pyramidal neurons survived. However, in the DCM- and Hx-fraction-treated ischemia groups, we did not find any significant neuroprotection. In addition, we observed changes in astrocytes and microglia in the ischemic CA1. In the crude-extract, EA- and BU-fraction-treated ischemia groups, the distribution pattern and activity of the glial cells were similar to that found in the sham group. Discussion: Repeated supplements of crude-extract, EA- and BU-fractions of A. clathratum could protect neurons from I-R injury in the hippocampal CA1 induced by transient cerebral ischemia via decrease of glial activation.